Pembuktian, Alat Bukti Dan Batasan Hilangnya Status Kepemilikan Tanah (Kadaluwarsa Tanah) - Umami, Hafidhul; Ula, Lia Mar'atul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
Land law in Islam can be defined as Islamic laws regarding land and its relation to ownership rights (milkiyah), management (tasharruf), and distribution (tauzi’) of land.There are still many people around us who do not really understand about the expiration limit related to the status of land ownership. Both in terms of Islamic law and in terms of state law (civil law). This if left unchecked can trigger conflicts between communities, so that enlightenment and socialization are needed to the community in order to understand about evidence, tools can be used as evidence, and expiration limits related to land ownership status.